2D Graphene in Interface Engineering of 3D Graphene‐Based Thermal Management. Issue 2 (10th November 2020) - Zhao, Menghan; Feng, Xiaoqiang; Zhu, Wei; Guo, Wei; Wang, Gang; Liu, Zhiduo; Guo, Qinglei; Chen, Da
Abstract : Three‐dimensional graphene (3D‐Gr) has a unique construction and special thermal features, thus providing promising opportunities for application in thermal management devices. Herein, 2D graphene (2D‐Gr) is introduced as an interfacial layer in plasma‐assisted chemical vapor deposition (PACVD); then, in situ growth of 3D‐Gr is achieved on a germanium (Ge) substrate. Systematic experiments are conducted to study and analyze the synthesis mechanism. Finally, the obtained 2D/3D‐Gr integrations are developed for the application in high‐performance thermal management. By measuring and comparing the thermal heating performance of the pure 3D‐Gr device and 2D/3D‐Gr device, it is determined that the combination of 3D‐Gr with 2D‐Gr significantly improves their thermal heating behavior, benefiting from the improved quality of 3D‐Gr assisted by the 2D‐Gr interfacial layer. The investigations offer an effective strategy for synthesizing high‐quality 3D‐Gr and 2D/3D‐Gr integrations, which pave the way for the development of high‐performance thermal management devices. Abstract : By comparing the thermal heating performance of the pure 3D graphene (3D‐Gr) device and 2D/3D graphene (2D/3D‐Gr) device, it is determined that the combination of 3D‐Gr with 2D‐Gr significantly improves their thermal heating behavior, benefiting from the improved quality of 3D‐Gr assisted by the 2D‐Gr interfacial layer.